The Role of Ethnic Minority Boarding Schools in Promoting Educational Equity in Vietnam: A Policy Analysis from Practice - Linh, Doan Nguyet; Thanh, Nguyen Quy (VNU Journal of Science: Education Research; Vol 41 No 3, 2025)
Inequality in education, especially in ethnic minority and mountainous areas, remains a major challenge in Vietnam. The ethnic boarding school model plays a key role in improving access and quality of education for ethnic minority students, aiming at the goal of educational equity according to the theoretical framework of Rawls and Sen (Equity of opportunity and need). The article analyzes the role of ethnic boarding schools from a policy perspective, based on organizational and investment practices, thereby proposing a number of policy recommendations. These recommendations aim at a more open, flexible, humane and effective ethnic education system, in line with the ethnic minority development strategy for the 2021-2030 period and the country's sustainable development goals.